2019
DOI: 10.1101/817627
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Learning to learn persistently modifies an entorhinal-hippocampal excitatory-inhibitory subcircuit

Abstract: SUMMARYThe neurobiology of psychological concepts like schema, and psychotherapeutic strategies of cognitive behavioral therapy (CBT) is poorly understood, partly because learning to process information confounds, and is rarely distinguished from acquiring content-specific memory. Learning to learn changes one’s overall information-processing ability, whereas neurobiological investigations typically focus on memory for content from particular experiences. We investigated entorhinal cortex-to-dentate gyrus neur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 70 publications
1
6
0
Order By: Relevance
“…While this does not support the anti-excitatory notion, suggested by prior work that did not distinguish DS L and DS M , our findings are consistent with the reduced population spike latency, increased population spike amplitude, and enhanced field excitatory postsynaptic potential (fEPSP) slope that were observed during medial perforant path (MPP) stimulation triggered by undifferentiated DS events (Bramham, 1998). Indeed, we have observed that training in a place avoidance task causes synaptic plasticity of the MPP synaptic response in the suprapyramidal molecular layers of DG, and potentiation of DS M but not DS L , corroborating the two pathways are distinctive and can be altered independently by experience (Chung et al., preprint).…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…While this does not support the anti-excitatory notion, suggested by prior work that did not distinguish DS L and DS M , our findings are consistent with the reduced population spike latency, increased population spike amplitude, and enhanced field excitatory postsynaptic potential (fEPSP) slope that were observed during medial perforant path (MPP) stimulation triggered by undifferentiated DS events (Bramham, 1998). Indeed, we have observed that training in a place avoidance task causes synaptic plasticity of the MPP synaptic response in the suprapyramidal molecular layers of DG, and potentiation of DS M but not DS L , corroborating the two pathways are distinctive and can be altered independently by experience (Chung et al., preprint).…”
Section: Discussionsupporting
confidence: 71%
“…One possibility is that separate neural circuits operate in parallel to perform each information processing task, but this does not appear to be the case for hippocampus. Rather, in hippocampus the same populations of excitatory and inhibitory neurons are organized such that network discharge patterns, sometimes called cell assemblies (Harris et al, 2003;Hebb, 1949) rapidly switch between different information processing modes, often in a winner-take-all fashion (Colgin, 2015;Kelemen and Fenton, 2010;Kelemen and Fenton, 2013;Kelemen and Fenton, 2016;Papale et al, 2016;Pastalkova et al, 2008;van Dijk and Fenton, 2018;Wu et al, 2017). We reported that position-representing CA1 ensemble spike trains switched between representing the current, local position and distant places, which during an active place avoidance task represented recollected locations of prior shocks (Dvorak et al, 2018).…”
Section: Introductionmentioning
confidence: 83%
“…These results could also stem from the fact that the alternation procedure is a spatial task, therefore, it engages the hippocampus as well, as evidence by neuronal activity activation during these tasks (Otto & Eichenbaum, 1992). Training in spatial or cognitive control tasks has been shown previously to increase neuronal excitability in the hippocampus (Chung et al, 2019; McKay et al., 2013; Oh et al., 2009). The PFC is interconnected with the hippocampus via different thalamic nuclei (Preston & Eichenbaum, 2013; Varela et al., 2013; Weel et al., 2019), making the possibility for transfer effects from the one brain region to the other plausible.…”
Section: Discussionmentioning
confidence: 98%
“…These results could also stem from the fact that the alternation procedure is a spatial task, therefore, it engages the hippocampus as well, as evidence by neuronal activity activation during these tasks (Otto and Eichenbaum, 1992). Training in spatial or cognitive control tasks have been shown previously to increase neuronal excitability in the hippocampus (Oh et al, 2009;McKay et al, 2013;Chung et al, 2019). The PFC is interconnected with the hippocampus via different thalamic nuclei (Preston and Eichenbaum, 2013;Varela et al, 2013;Weel et al, 2019), making the possibility for transfer effects from the one brain region to the other plausible.…”
Section: Effect Of Wm Training On Hpc Functionmentioning
confidence: 97%